Family violence associated with substance use in men who exercise violence - Deza Villanueva, Sabina (2013)
Relatively few studies conducted outside the United States, Canada and Europe that have examined the associations between alcohol use and intimate partner violence. And these studies have focused on the relationship between alcohol consumption by men and violence in them towards their partners. In general, these studies suggest that increased consumption of alcohol or drunkenness in men is associated with an increased risk of abusing their partners. This paper raises the need for research on psychoactive substance use in adult men practicing family violence and explicit research findings at national and international level. The topics covered are: defining variables linked to family violence associated with consumption of SPA, theoretical models of the relationship between domestic violence and alcohol abuse and finally a review of current studies on the matter. It is noted that in literature reviewed the analysis of the relationship between gender, drugs and violence is paramount, as the progress made by the studies of masculinities since the eighties have been very remarkable and address this in abundance, given the prominence of the violence in male behavior